Exploring the implementation of a novel, transdiagnostic, hybrid ecological momentary intervention for improving resilience in youth (EMIcompass): a process evaluation in the realist framework - Pätzold, Isabell; Gugel, Jessica; Schick, Anita; Rauschenberg, Christian; Hirjak, Dusan; Boecking, Benjamin; Doi, Lawrence; Schwannauer, Matthias; Reininghaus, Ulrich (Psychology and psychotherapy, 2025)
Objectives Previous research indicates that the hybrid compassion-focused intervention EMIcompass may reduce stress reactivity and improve quality of life. Our aim was to investigate what components of the intervention work for whom, how, and under which circumstances to contribute to the enhancement of resilience. Methods We conducted a process evaluation using a realist framework. First, we developed initial programme theories using compassion-focused interventions and ecological momentary intervention documents, in addition to conducting a focus group and an interview with an individual expert. Second, we tested the initial programme theories based on qualitative data from 20 participants. Third, we refined the programme theories by analysing and interpreting the data. Results We identified four programme components experienced as enhancing the activation of the soothing system and the application of compassion-focused principles. EMIcompass was perceived as lowering the burden of and barriers to treatment and facilitating the translation into daily life. Intra- and interpersonal context factors interacted with the mechanisms, leading to improvement in well-being, which was identified as a main outcome. Discussion The intervention worked by strengthening participants' soothing system and facilitating ecological translation leading to improved well-being. Adaptions to improve the intervention may allow for more flexibility in individual intervention trajectories acknowledging different needs and preferences.